Flexible Working Arrangement (FWA) Model: Reducing Congestion Levels and Work Stress and Increasing Work Productivity - Sultan, Zulkifli; Fachmi, Muhammad; Klimko, Roman (Jurnal Manajemen Bisnis, 2024)
Research aims: This research aims to analyze the impact of the flexible working arrangement (FWA) system in reducing traffic jams, reducing work stress, and increasing work productivity.Design/Methodology/Approach: This research uses a sample collection technique with purposive sampling by distributing questionnaires to 100 government and company employees and interviewing 5 informants from government employees. Data analysis uses SEM (structural equation model) with the AMOS analysis tool.Research findings: Flexible working arrangements (FWA) have an important role in reducing traffic jams, which can increase a person's work stress. Reducing traffic congestion has a positive impact on workers and decreases work stress. Despite flexible working arrangements (FWA), work congestion and stress do not influence work productivity.Theoretical Contribution/Originality: This research contributes to the science of human resource management and urban management related to HR work activities.Practitioners/Policy Implications: The results of this research become a source and basis for guidance in structuring work patterns to be more efficient and effective, i.e., working flexibly can reduce the level of traffic congestion.Research Limitations/Implications: The limitation to this research includes the very limited number of respondents and informants who cannot be met directly so the question-and-answer process is less in-depth. Moreover, the indicators for each variable are still lacking, while the references are still weak.